Proceedings of the 19th International Conference on Enterprise Information Systems 2017
DOI: 10.5220/0006312703410350
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Correlation between CK Metrics, Test Coverage and Mutation Score

Abstract: In this paper we investigate the correlation between test coverage, mutation score and object-oriented systems metrics. First we conducted a literature review to obtain an initial model of testability and existing object-oriented metrics related to testability. Thus we selected four open source system whose test cases were available and calculated the correlation between the metrics collected and the line coverage, branches coverage and mutation score. Preliminary results show that some CK metrics, which are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In order to generate the instance space of automated testing and investigate the research questions formulated in Section 1, the following steps are required [24], [37]:…”
Section: Instance Space Analysismentioning
confidence: 99%
“…In order to generate the instance space of automated testing and investigate the research questions formulated in Section 1, the following steps are required [24], [37]:…”
Section: Instance Space Analysismentioning
confidence: 99%
“…Afterward, the statistical test, independent t-test, was used to determine whether the ensemble meta-estimator, VoR, performed better than base regressors. Some researchers consider coverage metrics such as branch coverage as a basis for predicting test effectiveness [36,70].…”
Section: Prediction Models Evaluationmentioning
confidence: 99%
“…For each model, we measure and report four typical error metrics, including MAE, MSE, Root Mean-Squared Error (RMSE), Mean-Squared Logarithmic Error (MSLgE), and Median Absolute Error (MdAE). These metrics are given by Equations ( 8)- (12). In all equations, y ˆi is the predicted value of the ith sample, y i is the corresponding actual value for y ˆi and n is the number of samples.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…They concluded that code coverage is an appropriate means to determine test effectiveness. Cruz and Eler [12] have investigated the correlation between test coverage, mutation score, and object-oriented systems metrics. Their preliminary results show that some C&K metrics [13] strongly affects line coverage and mutation score.…”
Section: Test Effectiveness Measurementmentioning
confidence: 99%